2004
DOI: 10.1063/1.1646671
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigation of CS2 dissociation at 193 nm by means of product state-selective vacuum ultraviolet laser ionization and velocity imaging

Abstract: A branching ratio of 1.6 +/- 0.3 for S(3P)/S(1D) is obtained for the dissociation of CS2 with very low fluence 193 nm laser (less than 2 mJ/cm2), in which the S(3P) and S(1D) have been state-selectively ionized using VUV lasers at different wavelengths. The anisotropy parameters betamax(3P) = 0.8 and betamax(1D) = 1.9 indicate that these channels are preferentially populated at different geometries and the lifetime is very short.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 19 publications
3
33
0
Order By: Relevance
“…The branching ratio of both species at 193 nm (6.424 eV) has been the subject of several investigations. Recently, the value of the branching ratio of 1.66 ± 0.3 for S( 3 P )/S( 1 D) was published [19]. The present work yields a similar value of 2.8 ± 0.4 (c.f.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…The branching ratio of both species at 193 nm (6.424 eV) has been the subject of several investigations. Recently, the value of the branching ratio of 1.66 ± 0.3 for S( 3 P )/S( 1 D) was published [19]. The present work yields a similar value of 2.8 ± 0.4 (c.f.…”
Section: Introductionsupporting
confidence: 76%
“…The ratio of 2.8 ± 0.4 found in favor of of S(3s 2 3p 4 1 D) is in clear contradiction to earlier work, where S(3s 2 3p 4 3 P ) is the more abundant species. Waller et al reported a branching ratio S( 3 P J )/S( 1 S J ) = 2.8 ± 0.3 [83] and 1.6 ± 0.3 was reported by Xu et al [19], also in favor of S( 3 P ). However, the present value of 2.8 ± 0.4 in favor of the S(3s 2 3p 4 1 D) state agrees with that found by Yang et al [21,22].…”
Section: Photoionization Of S(3smentioning
confidence: 95%
See 2 more Smart Citations
“…The excited state bending frequency is nearly degenerate with that of the considerably weakened symmetric stretch, leading to combination bands of symmetric stretch and bend with peaks spaced by ∼400 cm −1 , each further split (∼30 cm −1 ) due to this near degeneracy (22 (24). From the peak widths in the absorption and S-atom action spectra, resonance lifetimes of less than 1 ps were estimated (23).…”
mentioning
confidence: 99%